2012
DOI: 10.1603/en12094
|View full text |Cite
|
Sign up to set email alerts
|

White-Tailed Deer Alter Specialist and Generalist Insect Herbivory Through Plant Traits

Abstract: Within a plant species, leaf traits can vary across environmental, genetic, spatial, and temporal gradients, even showing drastic differences within individuals. Herbivory can also induce variation in leaf morphology, defensive structure, and chemistry including nutritional content. Indirect effects of prior insect herbivory on later herbivores have been well documented, but the induction of trait changes after vertebrate herbivory has been little explored. Here, we examined how browsing of spicebush (Lindera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 48 publications
(42 reference statements)
2
26
1
Order By: Relevance
“…Deer browsing can reduce plant traits, such as plant height, number of shoots (Den Herder et al 2004), number of leaves per plant (Takagi and Miyashita 2012), and leaf N content (Lind et al 2012). Nonetheless, occasionally deer browsing may actually increase foliar nutrient content (Takagi and Miyashita 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deer browsing can reduce plant traits, such as plant height, number of shoots (Den Herder et al 2004), number of leaves per plant (Takagi and Miyashita 2012), and leaf N content (Lind et al 2012). Nonetheless, occasionally deer browsing may actually increase foliar nutrient content (Takagi and Miyashita 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Takatsuki and Itô (2009) showed that high densities of deer inhibited tree regeneration and favored understory plant communities composed of highly herbivory-tolerant and well-defended species. Furthermore, changes to plant properties induced by deer presence can have positive (Barrett and Stiling 2007; Takagi and Miyashita 2012) or negative (Lind et al 2012; Shimazaki and Miyashita 2002) effects on the attack of these plants by other herbivores. The direction of these indirect plant-mediated interactions induced by deer can be similar or different across different insect-feeding guilds (Poelman et al 2010; Viswanathan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, herbivory by one herbivore can alter the food quality of plants for other herbivores, positively or negatively affecting their performance, density, and/or patterns of herbivory (Gange and Brown 1989;Roininen et al 1997;Martinsen et al 1998;Nakamura et al 2003;Lind et al 2012). Many studies on these Bplant-mediated effects^have investigated plant parts (e.g., leaves and shoots) close to the site of herbivory (Danell and Huss-Danell 1985;Roininen et al 1997;Martinsen et al 1998;Nakamura et al 2003;Bailey and Whitham 2006;Lind et al 2012), on the assumption that induced responses tend to be stronger closer to the damage. In contrast, several authors have reported that herbivory by one herbivore can positively or negatively affect other herbivores that are distant from the damaged site due to changes in resource allocation at the whole-plant scale (Gange and Brown 1989;Bezemer et al 2003;Johnson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The overabundance of sika deer results in heavy herbivory pressure (e.g., browsing, bark stripping, grazing) on vegetation, especially on preferred plants such as willows (Salix udensis and Salix miyabeana). There is increasing evidence that cervid herbivory induces compensatory regrowth in plant parts close to those damaged by herbivory (Danell and Huss-Danell 1985;Roininen et al 1997;Bailey and Whitham 2006;Lind et al 2012). The regrowth response following cervid herbivory often facilitates insect herbivory (Danell and Huss-Danell 1985;Roininen et al 1997) because it provides new plant tissues, which tend to contain greater nitrogen and are often poorly defended (Danell and Huss-Danell 1985;Nakamura et al 2006).…”
Section: Introductionmentioning
confidence: 99%